PERBANDINGAN KINERJA PERBANKAN MELALUI RASIO KEUANGAN BERDASARKAN ASPEK RISK PROFILE, EARNINGS, DAN CAPITAL SEBELUM DAN SELAMA PANDEMI COVID-19 (Studi Pada Bank BUMN Konvensional) - Wibowo, Dimas Hary; Galuh, Ajeng Kartika (Contemporary Studies in Economic, Finance and Banking, 2022)
Financial ratios as an indicator of bank performance, in conventional state-owned banks show differences in performance between before and during the Covid-19 pandemic. This study aims to see whether there are conventional state-owned banks that have significant differences in performance between before and during the Covid-19 pandemic, as seen through the financial ratios. Financial ratios Non Performing Loan (NPL) and Loan to Deposit Ratios (LDR) as a projection from the Risk Profile aspect, Return on Asset (ROA), Return on Equity (ROE), and Net Interest Margin (NIM) as a projection from the Earnings aspect, as well as the Capital Adequacy Ratio (CAR) as a projection from the Capital aspect. The data analysis method is a different test used Paired Sample t-Test and Wilcoxon Signed Ranks Test. The study results indicate a decrease in performance based on aspects of Risk Profile, Earnings, and Capital in conventional state-owned banks. From the results of data analysis, it was also found that bank Mandiri showed significant differences in NPL, LDR, ROA, ROE, NIM, and CAR, bank BRI showed significant differences in NPL, LDR, ROA, and ROE, bank BNI showed significant differences in NPL, LDR, ROA, ROE, and NIM, as well as at bank BTN showed significant differences in LDR, ROA, and CAR.